Descriptive Study on Prevalence of Sensorineural Hearing Loss in Diabetes, Hypertensive Patients - Bomma Vijay Kumar; Ambati Rathna Kumari; Sravani Maryada; Shoban Babu (International Journal of Health and Clinical Research, 2021)
Introduction: The chronic diseases caused by genetics, life style, the environment and ageing itself are the key factors that affect health today; hence, we should concentrate our attention on our patients’ last years of life aimed at raising the number of elderly people in health, able to sustain their physical and mental functions.Aims :To study the incidence and degree of sensorineural hearing loss in diabetic, hypertensive patients. Materials and methods: This is a prospective observational study done for a period of 18 months. The study will be conducted on 50 subjects diagnosed with diabetes, 50 subjects diagnosed with hypertension and 50 subjects with both hypertension and diabetes and 50 normal subjects without hypertension and diabetes. All the subjects in the age group of 20-60 years with diagnosed diabetes, hypertension and normal subjects without hypertension and diabetes both males and females are included in study.Results: Of 100 patients in study age of the group with associated disease is statistically higher in the group without associated disease. It was found that out of 150 cases with hypertension or diabetes or both in present study 138 were in the age group of 40- 60 and only 12 cases were between age 20-40. Patients with hypertension (86%) were at higher risk of developing SNHL when compared to controls (0%). Duration of hypertension had a slight influence on developing SNHL as only 77% cases within 5 year duration had SNHL but 100% of cases with duration of hypertension more than 5 years had SNHL. Effect of diabetes on the SNHL in comparision to controls which showed 70% chance of having SNHL in diabetic cases. All the cases had only mild SNHL and no moderate or severe hearing loss.Conclusion: The importance of preventive processes that may reduce the mechanisms that trigger hearing aid degeneration induced by circulatory problems especially high blood pressure and high blood sugar, and the need for much more information on the regulation of the effects of these comorbidities on hearing are highlighted.